The role of individual self-study students work in course VI medical university in the professional preparation of doctors - Grubnik, V. V.; Koshel, Y. M.; Tkachenko, O. I. (Journal of Education, Health and Sport, 2017)
Implementing algorithms of the organization and evaluation of individual self-study students work of VI course aims to acquire well educational material that was not included in the theme. According to the work program on surgical diseases it was allocated 119 (46%) hours of self-study work from 259 total hours for students of 6 course. To prepare for practical training was given 71 hours (60%) of that time, and 48 hours (40%) should be used so that the student study himself the curriculum issues that have not been put to practical training topics. Individual self-study students work allows to learn educational material that was not included in the themes of practical training, to learn practical skills (curation of patients, primary surgical treatment, assistance during operation, the registration of medical documentation), to learn modern methods of professional information from the internet, what is a contemporary form of knowledge acquisition during self-study.